2020
DOI: 10.4491/eer.2020.380
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment of elemental carbon, ultrafine particles, and crystalline silica at highway toll booths

Abstract: Highway toll booth workers have been reported to be at an increased risk of occupational lung cancer. Moreover, insufficient studies have been performed on exposure assessment of workers at highway toll booths. Elemental carbon (EC), black carbon (BC), and respirable crystalline silica (RCS) concentrations were measured at highway toll booths in Gyeongsangbuk-do (Republic of Korea). The particle number (PN) concentration and size distribution of ultrafine particle were measured using three SMPS devices. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Of the limited research, a previous study showed that the RCS concentration of highway toll booth workers were below the detection limit 27 . Meanwhile, the GM RCS concentrations of workers who cultivated citrus and table grapes in farms in California, USA were as high as 0.08 and 0.02 mg m –3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of the limited research, a previous study showed that the RCS concentration of highway toll booth workers were below the detection limit 27 . Meanwhile, the GM RCS concentrations of workers who cultivated citrus and table grapes in farms in California, USA were as high as 0.08 and 0.02 mg m –3 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an increased occupational exposure to BC in a large group of workers including municipal household garbage collectors (Lee et al, 2015), traffic police (Shakya et al, 2016), underground tunnel construction workers (Galea et al, 2016), farmers (Stapleton et al, 2018;Sauvé et al, 2020), subway workers (Choi et al, 2019) and toll operators (Shin et al, 2021). According to these studies, BC exposure levels were high when working with dieselpowered equipment indoors such as underground tunnels or subway.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…S1(d)). A study done by Shin et al (2021) comparing the BC concentration at the same time inside and outside the tollbooth, showed that the GM concentration of BC inside booth (7.3 µg m -3 ) was 88% of the outside concentration (8.3 µg m -3 ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%